2020
DOI: 10.15847/obsobs14420201748
|View full text |Cite
|
Sign up to set email alerts
|

Rebuilding investigative journalism. Collaborative journalism: sharing information, sharing risk

Abstract: This article details the role of collaborative journalism during the process of rebuilding investigative journalism at its core thus assuring enduring investment in its quality. We will start by characterizing the concepts of investigative journalism and collaborative journalism, using leading scholars in both of these complementary areas; we will, then, identify the pressures that constrains investigative journalism, and analyse how journalistic collaboration has a potential for resistance that can pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 4 publications
0
4
0
1
Order By: Relevance
“…After the murders of the Maltese journalist Daphne Caruana Galizia in 2017 and the Slovakian journalist Ján Kuciak in 2018, the concern about the safety of European journalists grew (Coelho & Alves Rodrigues, 2020). This article has shown that Spanish, Italian, and Greek journalists do not perceive to be affected so much by violent threats as by a discursive form of threat, that has gained ground due to multiple factors.…”
Section: Discussionmentioning
confidence: 98%
“…After the murders of the Maltese journalist Daphne Caruana Galizia in 2017 and the Slovakian journalist Ján Kuciak in 2018, the concern about the safety of European journalists grew (Coelho & Alves Rodrigues, 2020). This article has shown that Spanish, Italian, and Greek journalists do not perceive to be affected so much by violent threats as by a discursive form of threat, that has gained ground due to multiple factors.…”
Section: Discussionmentioning
confidence: 98%
“…The technology that provides the means to filter and decrypt a volume of data with the gigantic dimension of the leak that the International Consortium of Investigative Journalists dealt with in the Panama Papers 7 is the same that made it possible to build the network that brought together the 370 reporters scattered in different parts of the world, bridging different cultures, different languages and providing each reporter with the protective shield that, especially in regions of the globe affected by attacks on freedom of expression, made it possible to dilute the risk for all the journalists involved (Coelho & Rodrigues, 2020;Lück & Schultz, 2019;Sambrook, 2017).…”
Section: The Challenge Of Technologymentioning
confidence: 99%
“…Navigating the inherent challenge of defining the concept of quality, especially if applied to journalism (Marinho, 2015), several authors draw a direct correlation between quality and investigative journalism 1 (Antelava, 2018;Birnbauer, 2019;Coelho & Rodrigues, 2020;Starkman, 2014;Tong, 2022). Concurrently, other scholars emphasise that the decline in quality caused by the sustainability crisis has had a particularly significant impact on investigative journalism (Burgh, 2021;Cagé, 2016;Hamilton, 2016;Hoxha, 2019;Jack, 2006;Knobel, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Iniciativas como las del International Consortium of Investigative Journalists (ICIJ), ProPublica y Journalism++ subrayan no sólo la creciente solidez de estas propuestas sino la diversidad de tipologías que admiten y la constante apuesta por nuevas narrativas de carácter multimedia y por novedosos procedimientos para presentar las ingentes cantidades de datos que son necesarias para generar contenidos periodísticos contrastados y fiables que aporten verdadero valor añadido (Parra, Edo y Marcos, 2017;Coelho y Rodrigues, 2020).…”
Section: Introductionunclassified